Pengaruh Kepercayaan, Keamanan, dan Kemudahan Penggunaan Terhadap Keputusan Pembelian pada GrabFood di Kota Batam - Afendi, Afendi; Inda Sukati (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aimed to examine the extent to which trust, perceived security, and ease of use of the GrabFood platform influence consumer transaction decisions in Batam City. The method used was descriptive quantitative, involving 204 respondents who had made purchases through GrabFood, selected through purposive sampling based on Jacob Cohen's formula to ensure representative results. Data were collected using a questionnaire and analyzed through a series of procedures, including validity and reliability testing, classical assumption checking, multiple linear regression, and hypothesis testing using t-tests and F-tests. The study findings revealed that trust contributed 22.0%, security 38.9%, and ease of use 23.2% to purchasing decisions. The coefficient of determination (R²) of 65.6% confirmed that these three factors simultaneously explained a significant portion of the variation in consumer purchasing behavior. Furthermore, t-tests and F-tests confirmed a positive and significant influence, both individually and collectively, on consumer decisions to use GrabFood.